Immune checkpoint inhibitors combined with concurrent chemoradiotherapy in locally advanced esophageal squamous cell carcinoma - Huang, Jiang-Qiong; Liang, Huan-Wei; Liu, Yang; Chen, Long; Pei, Su; Yu, Bin-Bin; Pan, Xin-Bin (Frontiers in Immunology, 2024)
Purpose This study aims to evaluate the efficacy of immune checkpoint inhibitors (ICIs) combined with concurrent chemoradiotherapy (CCRT) versus CCRT alone in patients with locally advanced esophageal squamous cell carcinoma. Materials and methods This retrospective cohort study included patients diagnosed with locally advanced esophageal squamous cell carcinoma who received either CCRT alone or CCRT combined with ICIs from April 2019 to February 2023. The primary endpoint was progression-free survival (PFS), and the secondary endpoint was overall survival (OS). Results A total of 101 patients were enrolled, with 58 undergoing CCRT alone and 43 receiving CCRT+ICI. The CCRT+ICI group demonstrated a higher complete response rate compared to the CCRT alone group (11.6% vs. 1.7%, P = 0.037). However, no significant difference was observed in 1-year PFS (58.9% vs. 55.2%; hazard ratio [HR] = 1.26, 95% confidence interval [CI]: 0.70-2.26; P = 0.445) or 1-year OS (70.8% vs. 75.9%; HR = 1.21, 95% CI: 0.58-2.53; P = 0.613) between CCRT+ICI and CCRT alone groups. The CCRT alone group experienced a higher incidence of leukopenia of any grade (93.1% vs. 76.7%, P = 0.039) but a lower incidence of pneumonitis of any grade (36.2% vs. 65.1%, P = 0.008). Conclusion CCRT+ICI may not lead to improved survival outcomes compared to CCRT alone in patients with locally advanced esophageal squamous cell carcinoma. These findings indicate the need for further investigation into this treatment approach.